2022
DOI: 10.4103/ams.ams_77_22
|View full text |Cite
|
Sign up to set email alerts
|

Role of Magnetic Resonance Imaging in Temporomandibular Joint Ankylosis - An Evaluative Study

Abstract: Introduction Temporomandibular joint (TMJ) ankylosis is a pathologic condition where the mandible is fused to the fossa by bony or fibrotic tissues. Haemorrhage is one of the major complications during TMJ surgery especially in ankyloses due to altered anatomy. The aim of the study was to analyse the proximity of the vasculature to the TMJ region in TMJ ankylosis patients using magnetic resonance imaging (MRI) Materials and Methods: Noncontrast-enhanced MRI images of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Studies have shown that the internal maxillary artery runs 3 mm medial to the mid-sigmoid notch [ 13 ]. Prasad et al [ 14 ] in their study have analyzed the mean distance of the internal maxillary artery from the ankylotic mass. It was found to be on an average of 4 mm from the medial edge of the ankylotic mass.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the internal maxillary artery runs 3 mm medial to the mid-sigmoid notch [ 13 ]. Prasad et al [ 14 ] in their study have analyzed the mean distance of the internal maxillary artery from the ankylotic mass. It was found to be on an average of 4 mm from the medial edge of the ankylotic mass.…”
Section: Discussionmentioning
confidence: 99%